Role for Conserved Residues of Sindbis Virus Nonstructural Protein 2 Methyltransferase-Like Domain in Regulation of Minus-Strand Synthesis and Development of Cytopathic Infection - Mayuri (American Society for Microbiology (ASM), 2008)
The plus-strand RNA genome of Sindbis virus (SINV) encodes four nonstructural proteins (nsP1 to nsP4) that are involved in the replication of the viral RNA. The ∼800-amino-acid nsP2 consists of an N-terminal domain with nucleoside triphosphatase and helicase activities and a C-terminal protease domain. Recently, the structure determined for Venezuelan equine encephalitis virus nsP2 indicated the presence of a previously unrecognized methyltransferase (MTase)-like domain within the C-terminal ∼200 residues and raised a question about its functional importance. To assess the role of this MTase-like region in viral replication, highly conserved arginine and lysine residues were mutated to alanine. The plaque phenotypes of these mutants ranged from large/wild-type to small plaques with selected mutations demonstrating temperature sensitive lethality. The proteolytic polyprotein processing activity of nsP2 was unaffected in most of the mutants. Some of the temperature-sensitive mutants showed reduction in the minus-strand RNA synthesis, a function that has not yet been ascribed to nsP2. Mutation of SINV residue R615 rendered the virus noncytopathic and incapable of inhibiting the host cell translation but with no effects on the transcriptional inhibition. This property differentiated the mutation at R615 from previously described noncytopathic mutations. These results implicate nsP2 in regulation of minus-strand synthesis and suggest that different regions of the nsP2 MTase-like domain differentially modulate host defense mechanisms, independent of its role as the viral protease.